The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1111/j.1432-1033.1986.tb10073.x
|View full text |Cite
|
Sign up to set email alerts
|

On the oxidation pathways of the mitochondrial bc1 complex from beef heart

Abstract: We have investigated the oxidation of the reduced ubiquinol : cytochrome c reductase (bcl complex) isolated from beef heart mitochondria. The oxidation of cytochrome cl by both potassium ferricyanide and cytochrome c in the ascorbate-reduced bcl complex is not a first-order process. This is taken as evidence that cytochrome cI is in rapid equilibrium with the Rieske iron-sulphur center. Among the several inhibitors tested, only 5-n-undecyl-6-hydroxy-4,7-dioxobenzothiazole and stigmatellin are seen to affect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
2

Year Published

1987
1987
2004
2004

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 36 publications
3
6
2
Order By: Relevance
“…Moreover, Rich and co-workers (19) have concluded from their recent studies that there is no detectable ubisemiquinone at the Q O site, thus making the proposed chemistry of bifurcated QH 2 oxidation at the Q O site of the Q cycle hypothesis even more complicated. These recent data agree with our previous results (13,14) as well as with those of Palmer and co-workers (20,21) that Q is not an obligatory electron carrier between cytochrome b and ISP/c 1 . In the Q cycle terminology, the complex III inhibitors binding near b H (e.g.…”
Section: Resultssupporting
confidence: 83%
“…Moreover, Rich and co-workers (19) have concluded from their recent studies that there is no detectable ubisemiquinone at the Q O site, thus making the proposed chemistry of bifurcated QH 2 oxidation at the Q O site of the Q cycle hypothesis even more complicated. These recent data agree with our previous results (13,14) as well as with those of Palmer and co-workers (20,21) that Q is not an obligatory electron carrier between cytochrome b and ISP/c 1 . In the Q cycle terminology, the complex III inhibitors binding near b H (e.g.…”
Section: Resultssupporting
confidence: 83%
“…The cytochrome c 1 concentration was determined from the difference spectrum of the ascorbate-reduced versus ferricyanide-oxidized enzyme, using an extinction coefficient of 17.5 mM Ϫ1 cm Ϫ1 at 553-539 nm (12). Cytochrome b concentration was determined from the difference spectrum of the sodium dithionite-reduced minus ascorbate-reduced enzyme using an extinction coefficient of 25 mM Ϫ1 cm Ϫ1 at 563-578 nm (13). The activity of this stock solution of enzyme was stable for a week at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Correlations between an unusual response to one bc 1 inhibitor and the sequence of the cytochrome b protein are most convincing when they combine sequence analysis in related s p e o e s with the information derived from mutants In the case of the natural resistance of fish to fumculosln [90], the results of a selected screening of fumculosin sensitivity m animal m l t o c h o n d n a suggested that the substitution of the conserved alanme 126 with the bulky m e t h l o n m e in the fish protein (Fig 1) is probably responsible for a substantial increase m the tltre of this inhibitor relatwe to normally sensltwe s p e o e s (Table V and R e f 90) Natural resistance in the plant mItochondnal bc t complex [142] could also be correlated with the exchange of A126 with the bulkier V m the cytochrome b sequence (Fig 2 and R e f 90) The buried location of position 126 within the transmembrane sector of hehx C (Fig 1) may account for the 'hybrid' effects of fumculosln, which effects both center i and center o [90,114,[143][144][145][146] Note that the proteins having a bulky amino a o d at poslt~on 126 also show resistance to U H D B T (Table V), which xs a center o inhibitor that shares with funlculosm the property of effectlng both qulnone sites [113,114,143,144] An interesting property of funlculosln is its remarkable species specificity, even among mammals [143,147] The volume pattern and the comparison of the sequences of sensltwe and resistant species suggested previously that position 194 may also be revolved in funlculosln binding [90] By inspecting the aligned sequences, we noticed that the rabbit protein shows the substitution of alanine 194 with a bulkier vahne residue (Fig 1) Hence, rabbit mltochondrla were expected to be quite resistant to funlculosin, which would explain why rabbits are resistant to this drug in vwo [147] This ~s indeed the case, since the inhibitory potency of funlculosln on the ublqumol cytochrome c reductase actwlty is about 60-fold lower for m l t o c h o n d n a ~solated from rabbit than those from sensltwe mammals (Table V) The cytochrome b proteins of zebra and donkey also have vahne at position 194 (Fig 1 and R e f 32) and differ from that of pig, a...…”
Section: I -D N a T U R A L Resistance As A Source O F N E W S T R mentioning
confidence: 99%